Effective Heuristics for Matchings in Hypergraphs - Dufossé, Fanny; Kaya, Kamer; Panagiotas, Ioannis; Uçar, Bora (Analysis of Experimental Algorithms, 2019)
The problem of finding a maximum cardinality matching in a d-partite, d-uniform hypergraph is an important problem in combinatorial optimization and has been theoretically analyzed. We first generalize some graph matching heuristics for this problem. We then propose a novel heuristic based on tensor scaling to extend the matching via judicious hyperedge selections. Experiments on random, synthetic and real-life hypergraphs show that this new heuristic is highly practical and superior to the others on finding a matching with large cardinality.